A note on integral modification of the Meyer-König and Zeller operators. (2nd June 2003) - Gupta, Vijay; Kumar, Niraj
Abstract : Guo (1988) introduced the integral modification of Meyer-Kö nig and Zeller operatorsM ˆ n and studied the rate of convergence for functions of bounded variation. Gupta (1995) gave the sharp estimate for the operatorsM ˆ n . Zeng (1998) gave the exact bound and claimed to improve the results of Guo and Gupta, but there is a major mistake in the paper of Zeng. In the present note, we give the correct estimate for the rate of convergence on bounded variation functions.